Characteristics of Fruit Jelly Candy (Study of The Proportion of Siwalan Juice (Borassus flabellifer) and Beetroot (Beta vulgaris L) Juice with Sorbitol Addition) - Ulya Sarofa; Ratna Yulistiani; Dianti Alfiana; Rani Ismuningtyas (Future Science, 2022)
Siwalan is a local fruit that has nutritional content and has not been processed. The addition of beetroot root juice to the siwalan jelly candy was expected to improve sensory and chemical characteristics such as increasing antioxidant activity. This study aims to determine the effect of the proportion of siwalan juice: beetroot juice and the addition of sorbitol on the characteristics of the siwalan fruit jelly candy. This study used a completely randomized design (CRD) with a two-factor factorial pattern. The first factor was the proportion of siwalan juice: beetroot juice (90:10, 80:20, and 70:30). While the second factor was the addition of sorbitol 50%, 60%, and 70%. The data obtained were tested using ANOVA and continued with the DMRT test. The results showed that the treatment of siwalan juice: beetroot juice (90:10) with a sorbitol concentration of 70% was the best treatment with a water content value of 14.33%, ash content 1.09%, vitamin C content 8.75 mg/100g, antioxidant activity 56.63%, total phenol 7.41 mg TAE/gr, gel strength 13.13 N, and organoleptic test including color 4.68 (slightly like), taste 4.72 (slightly like), aroma 3.92 (slightly like), texture 3.68 (slightly like).